A Study on The Effects of Incentive Strategies on Work Engagement for “Teachers with Dual Professional Qualifications” in Private Universities in Shaanxi, China: Self-Efficacy AS Mediator - Zhao, Wei; Nenyod, Boonmee; Lu, Leehsing (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study aims to (1) examine the effect of incentive strategies on the work engagement of teachers with dual professional qualifications at private universities in Shaanxi Province, (2) analyze the relationships among economic incentives, career development incentives, training incentives, self-efficacy, and work engagement, and (3) explore how dual professional qualifications influence the effectiveness of these incentive strategies. The study collected 403 valid responses from 422 distributed questionnaires, yielding a 95.5% response rate. Participants were dual-qualified teachers from four private universities in Shaanxi, representing various disciplines. Stratified random sampling was used, ensuring diversity by gender, teaching experience, and academic background. Data was collected from March to May 2024 using a structured questionnaire. The scales showed high internal consistency (Cronbach’s α = 0.75–0.91) and strong reliability (CR > 0.80). Confirmatory factor analysis confirmed good model fit (χ²/df=2.45, CFI=0.91, TLI=0.90, RMSEA=0.054). The results revealed: 1. Economic, career development, and training incentives positively impact work engagement, with self-efficacy acting as a key mediator. 2. Dual professional qualifications strongly influenced the link between self-efficacy and work engagement, with dual-qualified teachers showing a more potent effect. 3. University-enterprise cooperation further increased teachers' work engagement by providing practical, real-world experiences. The findings enhance the theoretical understanding of incentive systems in higher education and offer practical recommendations for improving incentive mechanisms, career development programs, and university-industry collaborations in private universities.